Assessing Science Teachers’ Pedagogical Content Knowledge (PCK) in the Context of Understanding about Instructional Strategies - Heffi Alberida; Yosi Laila Rahmi; Muhyiatul Fadilah; Sa'diatul Fuadiyah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aimed to investige the gap between teachers' perception and practice of implementing the learning models by biology teachers. This article applied descriptive quantitative research design, with the Learning Models Questionnaire (LMQ) used to collect the data. The research subjects were 78 teachers who are members of Science Subject Teachers’ Meeting (SSTM) and the object of research was the understanding and application of learning models. The results showed that there were three gaps related to the understanding and implementation of the biology learning model. First, there was around 70% of biology teachers stated that they understood learning models, however just only 25% of teachers understood the need for rational selection of models, building reaction systems, providing learning tools, and managing time. Second, teachers have good knowledge of learning models, but less than 35% of teachers implement them in class. Third, teachers have perceptions about the characteristics of the learning model, namely syntax, objectives, and learning tools, but in practice some teachers still do not understand syntax, do not know the purpose of the model being applied, and do not prepare learning tools that support the implementation of the learning model. There are a number of gaps between the understanding and practice of learning models by biology teachers, it is important to follow up as an indication of the teacher's pedagogical competence is still weak in understanding and applying learning models. These insights will impact the development of teachers' understanding of the learning models.